A new agent for the treatment of noninfectious uveitis: rationale and design of three LUMINATE (Lux Uveitis Multicenter Investigation of a New Approach to Treatment) trials of steroid-sparing voclosporin - Eddy Anglade (Dove Medical Press, 2008)
Eddy Anglade1, Launa J Aspeslet2, Sidney L Weiss11Lux Biosciences Inc., Jersey City, NJ, USA; 2Isotechnika Inc., Edmonton, AB, CanadaAbstract: Uveitis is an inflammatory, putative Th1-mediated autoimmune disease that affects various parts of the eye and is a leading cause of visual loss. Currently available therapies are burdened with toxicities and/or lack definitive evidence of efficacy. Voclosporin, a rationally designed novel calcineurin inhibitor, exhibits a favorable safety profile, a strong correlation between pharmacokinetic and pharmacodynamic response, and a wide therapeutic window. The LUMINATE (Lux Uveitis Multicenter Investigation of a New Approach to TrEatment) clinical development program was initiated in 2007 to assess the safety and efficacy of voclosporin for the treatment, maintenance, and control of all forms of noninfectious uveitis. If LUMINATE is successful, voclosporin will become the first Food and Drug Administration-approved corticosteroid-sparing agent for this condition.Keywords: voclosporin, calcineurin inhibitors, LX211, LUMINATE trials, ophthalmic diseases, uveitis, ISA247